Morphological description and pollen viability of Nothofagus nervosa (Nothofagaceae) - García, Luz; Rivero, Magaly; Droppelmann, Fernando (BOSQUE, 2017)
Understanding the biology of pollen is necessary to optimize the reproduction of plants and the successful implementation of conservation and breeding programs. In order to have information on the morphological characteristics and pollen viability in Nothofagus nervosa, male flowers of trees established in a clonal seed orchard were collected. Morphological characterization of pollen was carried out from observations under light microscope and scanning electron microscope. Motic Images Plus 2.0 software was used for measurements. Viability was assessed by in vitro germination, germination in vivo and staining with p-phenylenediamine. The pollen size of these species ranges from medium to large and the shape is from sub-oblate to oblate spheroid. Initial viability by in vitro germination ranged from 17.1 to 84.9 %; with the staining method, it ranged from 70.7 to 99.3 %; using in vivo germination it was calculated between 77.4 and 97.1 %. There was a strong correlation between in vitro germination and in vivo germination, but there was no correlation between viability calculated by the staining method and that calculated by germination in vivo; whereby the in vitro method is recommended to assess both viability and longevity of pollen of this species. According to assessments by in vitro germination, pollen lost its viability within a period of eight days stored at room temperature.